Chemical Composition and Facieses of Water from Vaskareh Village, Damavand: Implication for Industrial, Agricultural and Human Consumptions - Fazli, Leila; Senemari, Saeedeh (International Journal of Geography and Geology, 2015)
The study region is located in Vaskareh, Rudhen, Damavand, in Tehran Province in the 1:100,000 map of east of Tehran. Formations of Shemshak, Karaj, Fajan, alluviums and alluvial fans of this area have outcrops in this region. Ions and cations were concentrated in this region due to severe tectonic events and rock variation. Three springs, two water reservoirs, and three wells were sampled to identify chemical type and facieses of water of Vaskareh. This sampling was taken in two turns in 2013 and 2014. Radial vectors and Piper charts were used to determine hydro chemical type and facieses of water. Finally, it was found that the samples were from bicarbonate calcite chemical types. Villax and sodium solution percentage (SSP) and alkalinity degree (RSC) and two criteria of SAR (sodium danger) and electrical conductivity (salinity danger) were used to classify water quality for agricultural applications, which water quality was suitable for agriculture in most points. Water quality for industrial use was evaluated for hardness and Langelier factor. It was unsuitable for industrial applications. Schoeller Chart showing that the water was indeed good for human consumption.